IDENTIFICATION OF SECONDARY METABOLITES IN AJWA DATE SEED EXTRACT (PHOENIX DACTYLIFERA L.) USING PHYTOCHEMICAL SCREENING, UV-VIS, FTIR, AND GC-MS METHODS - Maqhfirah Amiruddin; Rahmawati Rahmawati; Chusnul Chotimah; Alhady Putra Vebryansyah (FKG ULM, 2026)
ABSTRACT: Previous studies concluded that Ajwa date (Phoenix Dactylifera L.) seed extract significantly reduced the roughness of acrylic resin plates used as denture bases, and has the potential to be used as a raw material for denture cleaning tablets. Several previous studies also showed that Ajwa date seeds contain various secondary metabolites, such as phenolic compounds and flavonoids, which have the potential as antioxidants and other bioactive agents. However, most of these studies were still limited to the use of specific analytical methods separately, such as phytochemical screening or chromatographic analysis, without a comprehensive integrated approach. Objective: To identify the levels of active secondary metabolites in ethanol extract of Ajwa date seeds using a comprehensive method with phytochemical screening, UV-Vis, FTIR, and GC-MS. Results: Ajwa date seeds were found to contain alkaloids, flavonoids, phenolics, tannins, and saponins. UV-Vis analysis showed consistent levels of polyphenols, tannins, and flavonoids. FTIR analysis showed that Ajwa date seeds are a rich natural source of polysaccharides, lipids, and phenolic compounds, and GC-MS results revealed various secondary metabolites detected at various retention times, rich in essential fatty acids, esters, and phenolic derivatives. All test methods were repeated three times. Conclusion: The combination of the four analytical methods complemented each other in identifying and confirming the presence of secondary metabolites in Ajwa date seed extract, thus providing a comprehensive picture of its chemical composition and potential bioactivity. Keywords: Ajwa date seeds, Phytochemical screening, UV-Vis, FTIR, GC-MS